2015
DOI: 10.1242/dev.113902
|View full text |Cite
|
Sign up to set email alerts
|

Activin signaling balances proliferation and differentiation of ovarian niche precursors and enables adjustment of niche numbers

Abstract: How the numbers of niches and resident stem cells within a particular organ are determined during development and how they may be modulated or corrected is a question with significant medical implications. In the larval ovary of Drosophila melanogaster, somatic precursors for niches, and germ cells that will become germline stem cells, co-develop. Somatic precursors proliferate during the first 3 days of larval development. By mid-third instar, adult terminal filament (TF) ( part of the germline stem cell nich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
0
23
1
Order By: Relevance
“…To follow TF cell accumulation and stack formation we used anti-Engrailed (En), which specifically stains TF cells [27]. At LL3, TF cells in WT or heterozygous ovaries were already stacked to form the adult number of niches (Fig 1H, Table 1) [8,12,28]. By contrast, TF formation was defective in cg mutants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To follow TF cell accumulation and stack formation we used anti-Engrailed (En), which specifically stains TF cells [27]. At LL3, TF cells in WT or heterozygous ovaries were already stacked to form the adult number of niches (Fig 1H, Table 1) [8,12,28]. By contrast, TF formation was defective in cg mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Vital dye staining (Propidium Iodide, PI) indicated that cell death did not increase in cg -mutant ovaries (of 18 cg 1 /cg KG00882 ovaries, 16 were not labeled by PI at all, and 2 had 1–3 dead cells, a similar level to WT ovaries)[8]. On the other hand, phospho-Histone H3 (pH3) staining, which marks mitotic cells, was significantly decreased in cg -mutants (0.15±0.03 pH3-positive cells per 1 μm 3 in WT ovarian volume, n = 21, as compared to 0.08±0.02 per 1 μm 3 in cg 1 /cg KG00882 ovaries, n = 14, t-test p-value 1.35e-6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations